GlcNAc-terminated glycodendrimers form defined precipitates with the soluble dimeric receptor of rat natural killer cells, sNKR-P1A - Bezouska, K; Kren, V; Kieburg, C; Lindhorst, T K (FEBS letters, 1998)
Synthetic GlcNAc-terminated thiourea-bridged glycoclusters were found to be potent inhibitors of binding of the soluble dimeric receptor of rat natural killer cells, sNKR-P1A protein, to its high affinity ligand. Moreover, we have shown here that characteristic precipitation curves can be recorded upon mixing of the GlcNAc glycoclusters with sNKR-P1A. For the GlcNAc8 glycocluster the precipitation curve is biphasic, with high affinity and low affinity precipitates differing in their sensitivity towards GlcNAc-mediated inhibition of precipitation. Quantitative analyses of the precipitates indicate the occurrence of a single sugar binding site per sNKR-P1A subunit, and lead to a model of the most possible spatial arrangements of the glycocluster-receptor lattices. These results provide new tools for further studies on carbohydrate recognition by NKR-P1A.
Keywords: acetylglukosamin; Rats; Dimerization; ligandy; Killer Cells, Natural; sacharidové sekvence; Antigens, Surface; Lectins, C-Type; Glycoconjugates; dimerizace; Acetylglucosamine; NK Cell Lectin-Like Receptor Subfamily B; lektiny typu C; lektinové receptory NK-buněk - podrodina B; krysa rodu Rattus; glykokonjugáty; antigeny povrchové; Ligands; kompetitivní vazba; zvířata; chemická precipitace; Binding, Competitive; Chemical Precipitation; molekulární struktura; mannosidy; Mannosides; Solubility; Carbohydrate Sequence; buňky NK; rozpustnost; Molecular Structure; Animals